(untitled) (Boletin Médico de Postgrado, 2020)
With the aim of describing echocardiographic findings in type 1 diabetic patients with hyperglycemia admitted to the Intermediate Care Unit of the Hospital Central Universitario Dr. Antonio Maria Pineda during the December 2018-January 2019 period, a cross-sectional descriptive study was done in 25 patients with an average age of 20.28 ± 3.49 years, 56% were males, 92% were asymptomatic and had a mean time of diagnosis of 4.96 ± 3.29 years. The results show that 20% of patients had mild diastolic dysfunction and 44% regional motility alterations. Mean glycemic values of these patients was 209 mg/dL. Echocardiographic functional findings were not associated with time of diagnosis of diabetes. Subclinical findings of cardiovascular disease associated with persistent hyperglycemia was found in this group of patients It is important to implement measures that prevent micro and macrovascular complications of this disease.